MAKNA VISUAL DALAM FILM PENDEK “PUPUS – CANGKIR PROFESOR” (2025): REPRESENTASI BUDAYA LOKAL JAWA: Visual Meaning in the Short Film “Pupus – Cangkir Profesor” (2025): Representation of Javanese Local Culture - Shofani Azhari (Jurnal Dimensi DKV: Seni Rupa dan Desain, 2025)
Visual Meaning in the Short Movie “Pupus – Cangkir Profesor” (2025): Representation of Javanese Local Culture. Visual meaning in a short movie offers a unique framework to preserve and reinterpret local culture in the digital era. This study investigates the visual semiotic construction of Javanese cultural values in the short movie “Pupus – Cangkir Profesor” (2025) through Roland Barthes’s semiotic model of denotation, connotation, and myth, combined with Stuart Hall’s cultural representation theory. The methodology employs a qualitative descriptive approach, using repeated scene segmentation, identification of visual signs, interpretive analysis, and validation through literature and cultural expert discussions. The findings demonstrate that the movie transforms everyday objects, gestures, and domestic spaces into cultural signs that encode grief, memory, and reverence for intellectual figures. Cups, silence, ritual gestures, and sacred domestic interiors become cultural myths reflecting Javanese values of suwung (sacred emptiness) and lila legawa (graceful acceptance). The study concludes that short movies function as both aesthetic narratives and cultural archives, bridging traditional heritage and digital storytelling. This research contributes to the broader discourse on visual semiotics and film as a medium of cultural preservation in the digital era.